Sosialisasi Pengenalan Dunia Perguruan Tinggi dan Perencanaan Karier bagi Siswa SMK Mambail Futuh, Jenu, Tuban - Bambang Minto Basuki; Aditya Roby Setyawan (Jurnal Kemitraan Masyarakat, 2026)
Vocational high school students often face challenges in planning their future education and careers due to limited information about higher education opportunities, study programs, admission pathways, scholarships, and long-term career prospects. This condition was also identified among students of SMK Mambail Futuh, Jenu, Tuban, where many students tended to prioritize entering the workforce immediately after graduation without adequate career planning. This community service program aimed to enhance students’ understanding of higher education and support them in developing more structured educational and career plans. The program was implemented through educational outreach activities, including presentations, interactive discussions, question-and-answer sessions, and motivational sharing on higher education and career development. The materials covered types of higher education institutions, study program options, university admission systems, scholarship opportunities, self-assessment of interests and talents, and career planning strategies. The results indicated a significant improvement in students’ knowledge and awareness of higher education opportunities and career pathways. Students showed strong enthusiasm during discussions and demonstrated increased interest in exploring further education, scholarship programs, and future career opportunities. The program also contributed to strengthening students’ motivation and confidence in making informed decisions regarding their educational and professional futures. These findings suggest that communicative and contextual educational outreach can effectively support vocational students in preparing for higher education and career development, thereby contributing to the improvement of human resource quality and future workforce readiness.